At5g19540 Encodes a Novel Protein That Affects Pigment Metabolism and Chloroplast Development in Arabidopsis thaliana - Huang, Xing-Qi; Zhao, Lei; Rui, Jin-Di; Zhou, Chang-Fang; Zhuang, Zhong; Lu, Shan (Frontiers in Plant Science, 2017)
Chlorophylls and carotenoids not only function in photosynthesis and photoprotection but are also involved in the assembly of thylakoid membranes and the stabilization of apoproteins in photosystems. In this study, we identified a nuclear gene required for chlorophyll and carotenoid metabolism, namely, DWARF AND YELLOW 1 (DY1). Growth of the loss-of-function dy1 mutant was severely retarded, and the seedlings of this mutant accumulated significantly less amounts of both chlorophylls and carotenoids in cotyledons and rosette leaves, although genes related to pigment metabolism did not show corresponding fluctuation at the transcriptional level. In chloroplasts of the dy1 leaves, thylakoids were loosely packed into grana. The dy1 mutant also possessed severely impaired photosynthetic and photoprotective abilities. DY1 encodes a chloroplast stroma protein that is highly conserved in vascular plants. Our results demonstrated that after the full-length DY1 (53 kDa) was imported into the chloroplast and its N-terminal transit peptide was processed, the C-terminal end of this premature DY1 (42 kDa) was also removed during the maturation of rosette leaves, resulting in a 24-kDa mature peptide. Our blue native PAGE and Western blot analyses showed the presence of both premature and mature forms of DY1 in protein complexes. The involvement of DY1 in chloroplast development is discussed.